Modified rare earth mineral anion indoor wall material coating

By introducing modified rare earth mineral negative ion powder and modified graphene oxide into the coating, the shortcomings of existing coatings in antibacterial, anti-mold and improving indoor air quality are solved, and the coating is efficiently anti-bacterial, anti-mold and anti-mold of the coating. Air purification effect.

CN119463623AInactive Publication Date: 2025-02-18HEBEI LUFA TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411460219.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-02-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing coatings have shortcomings in antibacterial and mildew resistance, which cannot produce negative ions and cannot effectively improve indoor air quality.

Method used

Modified rare earth mineral negative ion powder and modified graphene oxide are used to prepare a modified rare earth mineral negative ion indoor wall coating through a specific preparation method. The coating consists of epoxy resin, polyurethane resin, modified negative ion powder, modified graphene oxide, etc., and has excellent negative ion release ability and stability.

Benefits of technology

This coating not only has excellent antibacterial and mildew resistance, but can effectively inhibit the growth of bacteria and mold, but also continuously release negative ions, improve indoor air quality, and improve the wear, chemical and weather resistance of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the field of building decoration materials, and particularly discloses a modified rare earth mineral anion indoor wall material coating. The preparation method comprises the following steps: S1, weighing the raw materials; s2, adding epoxy resin and polyurethane resin into the diluent, and stirring to obtain mixed resin; s3, stirring the modified negative ion powder, the modified graphene oxide and deionized water to obtain mixed slurry; and S4, heating and stirring the mixed resin and the mixed slurry to obtain a mixture, adding a curing agent, a leveling agent and a curing accelerator into the mixture, heating and stirring to obtain a coating, and uniformly coating the surface of a base material with the coating to obtain the modified rare earth mineral anion indoor coating. The preparation method is simple, and the prepared modified rare earth mineral anion indoor wall material coating has good stability, antibacterial effect and antibacterial durability and is wider in practical application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of building decoration and furnishing materials, and more specifically, to a modified rare earth mineral negative ion indoor wall material coating. Background Art

[0002] Indoor air pollution is a hidden and serious health hazard. It mainly comes from the accumulation of harmful substances from multiple sources in a closed environment, including building materials, furniture, cleaning products, and substances released during combustion. These substances, such as volatile organic compounds (VOCs), suspended particulates, and gases produced by combustion, can have adverse effects on the respiratory and cardiovascular health of residents when exposed for a long time. In the process of interior decoration, paint is widely used for wall decoration, but there are some problems with conventional paint. First, the surface of the coating formed is susceptible to microbial invasion, resulting in plaque formation and reduced adhesion of the coating. Secondly, conventional paint has no positive effect on indoor air quality and cannot effectively reduce the concentration of substances such as volatile organic compounds (VOCs). In addition, conventional paints are prone to mildew and corrosion when facing humid environments, affecting the durability of the coating and the overall life of the building.

[0003] At present, the research and development of coatings on the market mainly focuses on basic properties, such as strength, adhesion, waterproof performance and appearance decoration. There are still limitations in the functional expansion of coatings, especially in anti-bacteria, anti-mildew and improving indoor air quality. Based on the above statement, the present application provides a modified rare earth mineral negative ion indoor wall material coating and a preparation method thereof. Summary of the invention

[0004] In order to solve the technical problems that existing coatings have poor antibacterial and anti-mildew properties, cannot generate negative ions, and cannot improve the indoor environment, the present application provides a modified rare earth mineral negative ion indoor wall material coating and a preparation method thereof.

[0005] In the first aspect, the present application provides a modified rare earth mineral negative ion indoor wall material coating, comprising the following raw materials in parts by weight: 50-70 parts of epoxy resin, 10-15 parts of polyurethane resin, 15-25 parts of modified negative ion powder, 8-12 parts of modified graphene oxide, 15-20 parts of curing agent, 1-4 parts of curing accelerator, 10-15 parts of diluent, 0.5-2.0 parts of leveling agent, and 25-40 parts of deionized water.

[0006] Preferably, the modified anion powder is prepared by the following method: A1. Weigh 2.0-6.0 parts of cerium nitrate, 0.5-1.0 parts of cobalt nitrate, 1.5-3.5 parts of lanthanum nitrate and 40-60 parts of deionized water, and mix them uniformly to obtain a mixed solution; A2. Evenly mix the mixed solution, mixed powder and mixed acid in a mass ratio of 10:1-4:2-6, heat to 80-100°C, stir for 1-2h, let stand for 2-3h, extract, dry the material, ball mill and calcine to obtain negative ion powder; A3. Treat the anion powder with alkali to obtain pretreated anion powder; mix the pretreated anion powder and the coupling agent solution in a mass ratio of 1:1-3, heat to 80-100°C, stir for 4-6h, filter, wash, and dry to obtain modified anion powder.

[0007] Preferably, the mixed powder is attapulgite and tourmaline powder in a mass ratio of 0.8-1.5:2.0-4.0.

[0008] Preferably, the mixed acid is acetic acid and oxalic acid in a mass ratio of 1:0.8-1.5.

[0009] Preferably, the calcination in step A2 specifically includes: first controlling the heating rate to 5-8°C / min, heating to 400-500°C, keeping warm for 30min-45min, then heating to 1000-1100°C at a rate of 10-15°C / min, and calcining for 3-5h.

[0010] Preferably, the alkali treatment is specifically as follows: preparing a sodium hydroxide solution with a mass fraction of 40-60%, mixing the sodium hydroxide solution and the negative ion powder in a mass ratio of 12:0.5-2.5, stirring at 45-60°C for 3-5h, then filtering, washing, and drying at 80-100°C to obtain the pretreated negative ion powder.

[0011] Preferably, the coupling agent solution is prepared by the following method: The coupling agent and deionized water are mixed evenly at a mass ratio of 2-5:100, and allowed to stand at room temperature for 1-2 hours. Then, 2-5% of the mass of the coupling agent, hexamethylene diisocyanate, is added, and ultrasonic dispersion is performed for 10-15 minutes to obtain a coupling agent solution.

[0012] Preferably, the coupling agent is isopropyl titanate triisostearate and γ-aminopropyl triethoxysilane in a mass ratio of 1-3:1-3.

[0013] Preferably, the modified graphene oxide is prepared by the following method: The graphene oxide is dispersed in a 40-60% by mass N, N-dimethylformamide solution, ultrasonically dispersed for 15-25 minutes, hydroxyethyl acrylate, hydroquinone and azobisisobutyronitrile are added, heated to 100-120° C., reacted for 6-8 hours, concentrated under reduced pressure, and dried to obtain modified graphene oxide.

[0014] In a second aspect, the present application provides a method for preparing a modified rare earth mineral negative ion indoor coating, comprising the following steps: S1, weighing the raw materials in parts by mass; S2, adding diluent to epoxy resin and polyurethane resin, stirring for 5-8 minutes to obtain mixed resin; S3, stirring the modified negative ion powder, modified graphene oxide and deionized water for 15-25 minutes to obtain a mixed slurry; S4, stirring the mixed resin and mixed slurry at 60-80° C. for 10-15 min to obtain a mixture, adding a curing agent, a leveling agent and a curing accelerator to the mixture, heating and stirring to obtain a coating, and uniformly coating the coating on the surface of the substrate to obtain a modified rare earth mineral anion indoor coating.

[0015] In summary, this application has the following beneficial effects: The present application adopts cerium nitrate, cobalt nitrate, and lanthanum nitrate to prepare a mixed solution by adding water and dispersing, and then the mixed solution, mixed powder, and mixed acid are treated together to prepare negative ion powder, and the negative ion powder is modified by coupling agent solution to obtain the final modified negative ion powder; the modified negative ion powder prepared in the present application has excellent negative ion release ability and good stability, and can maintain efficient negative ion release effect for a long time. Rare earth elements cerium, cobalt, and lanthanum are added to the negative ion powder. The three elements can promote the release of negative ions while significantly enhancing the mechanical properties, antibacterial, anti-corrosion, antioxidant and durability of the material; using attapulgite and tourmaline powder with high specific surface area as mixed powder can provide more reactive sites, which is conducive to the reaction of rare earth elements with the powder surface and improve the adsorption and dispersion performance of rare earth elements; using acetic acid and oxalic acid as mixed acid, it can form complexes with rare earth elements while achieving effective dissolution and dispersion, promote the reaction of rare earth elements, and improve the preparation efficiency of negative ion powder and the utilization rate of rare earth elements.

[0016] The present application disperses graphene oxide in an N,N-dimethylformamide solution, and functionally modifies the graphene oxide by adding hydroxyethyl acrylate, hydroquinone and azobisisobutyronitrile for reaction, wherein hydroxyethyl acrylate and hydroquinone can introduce different functional groups and chemical structures, which provide active sites for subsequent reactions while significantly enhancing the hydrophilicity, dispersibility and compatibility of graphene oxide with subsequent reaction raw materials.

[0017] The present application adopts epoxy resin and polyurethane resin as base materials, and prepares a coating by adding modified negative ion powder, modified graphene oxide and additives, and uniformly applies the coating on the surface of the substrate to obtain a modified rare earth mineral negative ion indoor coating; the coating obtained by the present invention has excellent wear resistance, chemical resistance and weather resistance, and the addition of modified negative ion powder and modified graphene oxide can give the coating excellent antibacterial and mildew resistance, effectively inhibit the growth of bacteria and mildew, and improve the surface performance of the coating. After drying, the coating can continuously release negative ions, improve indoor air quality, purify the air, and eliminate odors, which has a positive effect on improving the indoor environment. DETAILED DESCRIPTION

[0018] The present application is further described in detail below in conjunction with the examples. Unless otherwise specified, the materials, reagents, etc. used in the present invention can be obtained from commercial sources. Epoxy resin was purchased from Shandong Luxing Chemical Co., Ltd., CAS number: 61788-97-4, density: 1.2 g / cm³, grade: E-44, brand: Nantong Phoenix, solid content: 99%; polyurethane resin was purchased from Anhui Feimiao Chemical Co., Ltd., grade: FS-7, brand: Feimiao, solid content: 30±2%, density: 1.06 g / cm³, pH value: about 7.

[0019] Example 1 A modified rare earth mineral negative ion indoor coating, comprising the following raw materials in parts by weight: 50 parts of epoxy resin, 10 parts of polyurethane resin, 15 parts of modified negative ion powder, 8 parts of modified graphene oxide, 15 parts of curing agent, 1 part of curing accelerator, 10 parts of diluent, 0.5 parts of leveling agent, and 25 parts of deionized water.

[0020] Wherein, the modified anion powder is prepared by the following method: A1. Weigh 2.0 parts of cerium nitrate, 0.5 parts of cobalt nitrate, 1.5 parts of lanthanum nitrate and 40 parts of deionized water, and stir at 200 rpm for 8 min to obtain a mixed solution; A2. Mix the mixed solution, mixed powder and mixed acid in a mass ratio of 10:1:2, heat to 80°C, stir at 300 rpm for 2 hours, let stand for 3 hours, filter, and dry at 100°C for 4 hours to obtain the material, control the mass ratio of grinding medium, material and grinding solvent to 2.0:1:1.2, ball milling time 70 minutes, rotation speed 300 rpm, grinding medium is steel ball, steel ball diameter is 20 mm, grinding solvent is ethanol, then control the heating rate to 5°C / min, heat to 400°C, keep warm for 30 minutes, then heat to 1000°C at a rate of 10°C / min, calcine for 5 hours to obtain negative ion powder; A3. The negative ion powder is subjected to alkali treatment to obtain pretreated negative ion powder; the pretreated negative ion powder and the coupling agent solution are mixed in a mass ratio of 1:3, heated to 80°C, stirred at 300 rpm for 6 hours, then filtered, washed three times with deionized water, and dried at 60°C for 12 hours to obtain modified negative ion powder.

[0021] The mixed powder is attapulgite and tourmaline powder in a mass ratio of 0.8:2.0.

[0022] The mixed acid is acetic acid and oxalic acid in a mass ratio of 1:0.8.

[0023] Among them, the alkali treatment includes: preparing a sodium hydroxide solution with a mass fraction of 40%, mixing the sodium hydroxide solution and the negative ion powder in a mass ratio of 12:0.5, stirring at 45°C and a speed of 300rpm for 5 hours, then filtering, washing with ethanol 3 times, and drying at 80°C for 5 hours to obtain the pretreated negative ion powder.

[0024] Wherein, the coupling agent solution is prepared by the following method: The coupling agent and deionized water were mixed evenly in a mass ratio of 2:100, and allowed to stand at room temperature for 1 hour. Then, 5% of the mass of the coupling agent, hexamethylene diisocyanate, was added, and ultrasonic dispersion was performed for 15 minutes to obtain a coupling agent solution.

[0025] The coupling agent is isopropyl titanate triisostearate and γ-aminopropyl triethoxysilane in a mass ratio of 1:1.

[0026] Wherein, the modified graphene oxide is prepared by the following method: The mass ratio of graphene oxide to N,N-dimethylformamide solution was controlled to be 1:300, and graphene oxide was dispersed in 40% by mass N,N-dimethylformamide solution. The mixture was ultrasonically dispersed at 40 kHz for 25 min, and hydroxyethyl acrylate, hydroquinone and azobisisobutyronitrile were added. The mixture was heated to 100°C, reacted for 8 h, concentrated under reduced pressure, and dried at 60°C for 6 h to obtain modified graphene oxide, wherein the mass ratio of graphene oxide, hydroxyethyl acrylate, hydroquinone and azobisisobutyronitrile was 1:0.5:0.1:0.2.

[0027] Wherein, the diluent is butyl glycidyl ether.

[0028] The curing agent is 4,4'-diaminodiphenylmethane and triglycidyl isocyanurate in a mass ratio of 2:0.5.

[0029] Among them, the leveling agent is BYK-310.

[0030] Wherein, the curing accelerator is 2-methylimidazole.

[0031] A method for preparing a modified rare earth mineral negative ion indoor coating comprises the following steps: S1, weighing the raw materials in parts by mass; S2, adding a diluent to the epoxy resin and the polyurethane resin, stirring at 300 rpm for 8 min to obtain a mixed resin; S3, stirring the modified negative ion powder, modified graphene oxide and deionized water at 300 rpm for 25 min to obtain a mixed slurry; S4, stirring the mixed resin and mixed slurry at 60° C. and 200 rpm for 15 min to obtain a mixture, adding a curing agent, a leveling agent and a curing accelerator to the mixture, stirring at 50° C. and 300 rpm for 12 min to obtain a coating, and uniformly coating the coating on the surface of the substrate to obtain a modified rare earth mineral anion indoor coating.

[0032] Example 2 A modified rare earth mineral negative ion indoor coating, comprising the following raw materials in parts by weight: 70 parts of epoxy resin, 15 parts of polyurethane resin, 25 parts of modified negative ion powder, 12 parts of modified graphene oxide, 20 parts of curing agent, 4 parts of curing accelerator, 15 parts of diluent, 2.0 parts of leveling agent, and 40 parts of deionized water.

[0033] Wherein, the modified anion powder is prepared by the following method: A1. Weigh 6.0 parts of cerium nitrate, 1.0 parts of cobalt nitrate, 3.5 parts of lanthanum nitrate and 60 parts of deionized water, and stir at 300 rpm for 5 min to obtain a mixed solution; A2. Mix a mixed solution, a mixed powder and a mixed acid in a mass ratio of 10:4:6, heat to 100°C, stir at 400 rpm for 1 hour, let stand for 3 hours, filter, and dry at 100°C for 3 hours to obtain a material, control the mass ratio of grinding medium, material and grinding solvent to 1.5:1:0.8, ball milling time 70 minutes, rotation speed 400 rpm, grinding medium is steel ball, steel ball diameter is 10 mm, grinding solvent is ethanol, then control the heating rate to 8°C / min, heat to 500°C, keep warm for 45 minutes, then heat to 1100°C at a rate of 15°C / min, keep warm for 3 hours to obtain negative ion powder; A3. The negative ion powder is subjected to alkali treatment to obtain pretreated negative ion powder; the pretreated negative ion powder and the coupling agent solution are mixed in a mass ratio of 1:3, heated to 100°C, stirred at 400 rpm for 4 hours, then filtered, washed three times with deionized water, and dried at 80°C for 8 hours to obtain modified negative ion powder.

[0034] The mixed powder is attapulgite and tourmaline powder in a mass ratio of 1.5:4.0.

[0035] The mixed acid is acetic acid and oxalic acid in a mass ratio of 1:1.5.

[0036] Among them, the alkali treatment includes: preparing a sodium hydroxide solution with a mass fraction of 60%, mixing the sodium hydroxide solution and the negative ion powder in a mass ratio of 12:2.5, stirring at 60°C and 400rpm for 3h, then filtering, washing with ethanol 5 times, and drying at 100°C for 3h to obtain the pretreated negative ion powder.

[0037] Wherein, the coupling agent solution is prepared by the following method: The coupling agent and deionized water were mixed evenly in a mass ratio of 5:100, and allowed to stand at room temperature for 1 hour. Then, 2% of the mass of the coupling agent, hexamethylene diisocyanate, was added, and ultrasonic dispersion was performed for 10-15 minutes to obtain a coupling agent solution.

[0038] The coupling agent is isopropyl titanate triisostearate and γ-aminopropyl triethoxysilane in a mass ratio of 3:1.

[0039] Wherein, the modified graphene oxide is prepared by the following method: The mass ratio of graphene oxide to N,N-dimethylformamide solution was controlled to be 1:400, and graphene oxide was dispersed in N,N-dimethylformamide solution with a mass fraction of 60%. The dispersion was carried out at 60kHz for 15min, and hydroxyethyl acrylate, hydroquinone and azobisisobutyronitrile were added. The mixture was heated to 120°C, reacted for 6h, concentrated under reduced pressure, and dried at 80°C for 4h to obtain modified graphene oxide, wherein the mass ratio of graphene oxide, hydroxyethyl acrylate, hydroquinone and azobisisobutyronitrile was 1:0.7:0.4:0.4.

[0040] Wherein, the diluent is 1,6-hexanediol diglycidyl ether.

[0041] The curing agent is 4,4'-diaminodiphenylmethane and triglycidyl isocyanurate in a mass ratio of 2:0.8.

[0042] Among them, the leveling agent is Efka-3835.

[0043] Wherein, the curing accelerator is methyldiethanolamine.

[0044] A method for preparing a modified rare earth mineral negative ion indoor coating comprises the following steps: S1, weighing the raw materials in parts by mass; S2, adding a diluent to the epoxy resin and the polyurethane resin, stirring at 400 rpm for 5 min to obtain a mixed resin; S3, stirring the modified negative ion powder, modified graphene oxide and deionized water at 400 rpm for 15 min to obtain a mixed slurry; S4, stirring the mixed resin and mixed slurry at 80° C. and 300 rpm for 10 min to obtain a mixture, adding a curing agent, a leveling agent and a curing accelerator to the mixture, stirring at 70° C. and 400 rpm for 8 min to obtain a coating, and uniformly coating the coating on the surface of the substrate to obtain a modified rare earth mineral anion indoor coating.

[0045] Example 3 A modified rare earth mineral negative ion indoor coating, comprising the following raw materials in parts by weight: 60 parts of epoxy resin, 12 parts of polyurethane resin, 20 parts of modified negative ion powder, 10 parts of modified graphene oxide, 18 parts of curing agent, 2 parts of curing accelerator, 13 parts of diluent, 1.5 parts of leveling agent, and 35 parts of deionized water.

[0046] Wherein, the modified anion powder is prepared by the following method: A1. Weigh 4.0 parts of cerium nitrate, 0.8 parts of cobalt nitrate, 2.5 parts of lanthanum nitrate and 50 parts of deionized water, and stir at 250 rpm for 7 min to obtain a mixed solution; A2. Mix the mixed solution, mixed powder and mixed acid in a mass ratio of 10:2:4, heat to 90°C, stir at 350rpm for 1.5h, let stand for 2.5h, filter, dry at 100°C for 3.5h to obtain the material, control the mass ratio of grinding medium, material and grinding solvent to 1.8:1:1.0, ball milling time 60min, rotation speed 350rpm, grinding medium is steel ball, steel ball diameter is 20mm, grinding solvent is ethanol, then control the heating rate to 7°C / min, heat to 450°C, keep warm for 35min, then heat to 1050°C at a rate of 13°C / min, calcine for 4h to obtain negative ion powder; A3. The negative ion powder is subjected to alkali treatment to obtain pretreated negative ion powder; the pretreated negative ion powder and the coupling agent solution are mixed in a mass ratio of 1:2, heated to 90°C, stirred at 350 rpm for 5 hours, then filtered, washed three times with deionized water, and dried at 70°C for 10 hours to obtain modified negative ion powder.

[0047] The mixed powder is attapulgite and tourmaline powder in a mass ratio of 1.2:3.0.

[0048] The mixed acid is acetic acid and oxalic acid in a mass ratio of 1:1.2.

[0049] Among them, the alkali treatment includes: preparing a sodium hydroxide solution with a mass fraction of 50%, mixing the sodium hydroxide solution and the negative ion powder in a mass ratio of 12:1.5, stirring at 55°C and 350rpm for 4 hours, then filtering, washing with ethanol 5 times, and drying at 90°C for 4 hours to obtain the pretreated negative ion powder.

[0050] Wherein, the coupling agent solution is prepared by the following method: The coupling agent and deionized water were mixed evenly in a mass ratio of 3:100, and allowed to stand at room temperature for 1.5 hours. Then, 3% of the mass of the coupling agent, hexamethylene diisocyanate was added, and ultrasonic dispersion was performed for 12 minutes to obtain a coupling agent solution.

[0051] The coupling agent is isopropyl titanate triisostearate and γ-aminopropyl triethoxysilane in a mass ratio of 1:3.

[0052] Wherein, the modified graphene oxide is prepared by the following method: The mass ratio of graphene oxide to N,N-dimethylformamide solution was controlled to be 1:350, and graphene oxide was dispersed in N,N-dimethylformamide solution with a mass fraction of 50%. The mixture was ultrasonically dispersed at 50 kHz for 20 min, and hydroxyethyl acrylate, hydroquinone and azobisisobutyronitrile were added. The mixture was heated to 110°C, reacted for 7 h, concentrated under reduced pressure, and dried at 70°C for 5 h to obtain modified graphene oxide, wherein the mass ratio of graphene oxide, hydroxyethyl acrylate, hydroquinone and azobisisobutyronitrile was 1:0.6:0.2:0.3.

[0053] The diluent is butyl glycidyl ether and 1,6-hexanediol diglycidyl ether in a mass ratio of 1:1.

[0054] The curing agent is 4,4'-diaminodiphenylmethane and triglycidyl isocyanurate in a mass ratio of 2:0.7.

[0055] Wherein, the leveling agent is ethylene-methyl acrylate-glycidyl methacrylate copolymer.

[0056] Wherein, the curing accelerator is m-xylylenediamine.

[0057] A method for preparing a modified rare earth mineral negative ion indoor coating comprises the following steps: S1, weighing the raw materials in parts by mass; S2, adding a diluent to the epoxy resin and the polyurethane resin, stirring at 350 rpm for 7 minutes to obtain a mixed resin; S3, stirring the modified negative ion powder, modified graphene oxide and deionized water at 350 rpm for 20 min to obtain a mixed slurry; S4, stirring the mixed resin and mixed slurry at 70° C. and 250 rpm for 13 min to obtain a mixture, adding a curing agent, a leveling agent and a curing accelerator to the mixture, stirring at 60° C. and 350 rpm for 10 min to obtain a coating, and uniformly coating the coating on the surface of the substrate to obtain a modified rare earth mineral anion indoor coating.

[0058] Comparative Example 1 A modified rare earth mineral negative ion indoor coating, comprising the following raw materials in parts by weight: 50 parts of epoxy resin, 10 parts of polyurethane resin, 15 parts of modified negative ion powder, 8 parts of modified graphene oxide, 15 parts of curing agent, 1 part of curing accelerator, 10 parts of diluent, 0.5 parts of leveling agent, and 25 parts of deionized water.

[0059] Wherein, the modified anion powder is prepared by the following method: A1. Weigh 2.0 parts of cerium nitrate, 1.5 parts of lanthanum nitrate and 40 parts of deionized water, and stir at 200 rpm for 8 min to obtain a mixed solution; A2. Mix the mixed solution, mixed powder and mixed acid in a mass ratio of 10:1:2, heat to 80°C, stir at 300 rpm for 2 hours, let stand for 3 hours, filter, and dry at 100°C for 4 hours to obtain the material, control the mass ratio of grinding medium, material and grinding solvent to 2.0:1:1.2, ball milling time 70 minutes, rotation speed 300 rpm, grinding medium is steel ball, steel ball diameter is 20 mm, grinding solvent is ethanol, then control the heating rate to 5°C / min, heat to 400°C, keep warm for 30 minutes, then heat to 1000°C at a rate of 10°C / min, calcine for 5 hours to obtain negative ion powder; A3. The negative ion powder is subjected to alkali treatment to obtain pretreated negative ion powder; the pretreated negative ion powder and the coupling agent solution are mixed in a mass ratio of 1:3, heated to 80°C, stirred at 300 rpm for 6 hours, then filtered, washed three times with deionized water, and dried at 60°C for 12 hours to obtain modified negative ion powder.

[0060] The mixed powder is attapulgite and tourmaline powder in a mass ratio of 0.8:2.0.

[0061] The mixed acid is acetic acid and oxalic acid in a mass ratio of 1:0.8.

[0062] Among them, the alkali treatment includes: preparing a sodium hydroxide solution with a mass fraction of 40%, mixing the sodium hydroxide solution and the negative ion powder in a mass ratio of 12:0.5, stirring at 45°C and a speed of 300rpm for 5 hours, then filtering, washing with ethanol 3 times, and drying at 80°C for 5 hours to obtain the pretreated negative ion powder.

[0063] Wherein, the coupling agent solution is prepared by the following method: The coupling agent and deionized water were mixed evenly in a mass ratio of 2:100, and allowed to stand at room temperature for 1 hour. Then, 5% of the mass of the coupling agent, hexamethylene diisocyanate, was added, and ultrasonic dispersion was performed for 15 minutes to obtain a coupling agent solution.

[0064] The coupling agent is isopropyl titanate triisostearate and γ-aminopropyl triethoxysilane in a mass ratio of 1:1.

[0065] Wherein, the modified graphene oxide is prepared by the following method: The mass ratio of graphene oxide to N,N-dimethylformamide solution was controlled to be 1:300, and graphene oxide was dispersed in 40% by mass N,N-dimethylformamide solution. The mixture was ultrasonically dispersed at 40 kHz for 25 min, and hydroxyethyl acrylate, hydroquinone and azobisisobutyronitrile were added. The mixture was heated to 100°C, reacted for 8 h, concentrated under reduced pressure, and dried at 60°C for 6 h to obtain modified graphene oxide, wherein the mass ratio of graphene oxide, hydroxyethyl acrylate, hydroquinone and azobisisobutyronitrile was 1:0.5:0.1:0.2.

[0066] Wherein, the diluent is butyl glycidyl ether.

[0067] The curing agent is 4,4'-diaminodiphenylmethane and triglycidyl isocyanurate in a mass ratio of 2:0.5.

[0068] Among them, the leveling agent is BYK-310.

[0069] Wherein, the curing accelerator is 2-methylimidazole.

[0070] A method for preparing a modified rare earth mineral negative ion indoor coating comprises the following steps: S1, weighing the raw materials in parts by mass; S2, adding a diluent to the epoxy resin and the polyurethane resin, stirring at 300 rpm for 8 min to obtain a mixed resin; S3, stirring the modified negative ion powder, modified graphene oxide and deionized water at 300 rpm for 25 min to obtain a mixed slurry; S4, stirring the mixed resin and mixed slurry at 60° C. and 200 rpm for 15 min to obtain a mixture, adding a curing agent, a leveling agent and a curing accelerator to the mixture, stirring at 50° C. and 300 rpm for 12 min to obtain a coating, and uniformly coating the coating on the surface of the substrate to obtain a modified rare earth mineral anion indoor coating.

[0071] Comparative Example 2 A modified rare earth mineral negative ion indoor coating, comprising the following raw materials in parts by weight: 50 parts of epoxy resin, 10 parts of polyurethane resin, 15 parts of modified negative ion powder, 8 parts of modified graphene oxide, 15 parts of curing agent, 1 part of curing accelerator, 10 parts of diluent, 0.5 parts of leveling agent, and 25 parts of deionized water.

[0072] Wherein, the modified anion powder is prepared by the following method: A1. Weigh 2.0 parts of cerium nitrate, 0.5 parts of cobalt nitrate, 1.5 parts of lanthanum nitrate and 40 parts of deionized water, and stir at 200 rpm for 8 min to obtain a mixed solution; A2. Mix the mixed solution and the mixed powder in a mass ratio of 10:1, heat to 80°C, stir at 300 rpm for 2 hours, let stand for 3 hours, filter, and dry at 100°C for 4 hours to obtain the material, control the mass ratio of grinding medium, material, and grinding solvent to 2.0:1:1.2, ball milling time 70 minutes, rotation speed 300 rpm, grinding medium is steel ball, steel ball diameter is 20 mm, grinding solvent is ethanol, then control the heating rate to 5°C / min, heat to 400°C, keep warm for 30 minutes, then heat to 1000°C at a rate of 10°C / min, calcine for 5 hours to obtain negative ion powder; A3. The negative ion powder is subjected to alkali treatment to obtain pretreated negative ion powder; the pretreated negative ion powder and the coupling agent solution are mixed in a mass ratio of 1:3, heated to 80°C, stirred at 300 rpm for 6 hours, then filtered, washed three times with deionized water, and dried at 60°C for 12 hours to obtain modified negative ion powder.

[0073] The mixed powder is attapulgite and tourmaline powder in a mass ratio of 0.8:2.0.

[0074] Among them, the alkali treatment includes: preparing a sodium hydroxide solution with a mass fraction of 40%, mixing the sodium hydroxide solution and the negative ion powder in a mass ratio of 12:0.5, stirring at 45°C and a speed of 300rpm for 5 hours, then filtering, washing with ethanol 3 times, and drying at 80°C for 5 hours to obtain the pretreated negative ion powder.

[0075] Wherein, the coupling agent solution is prepared by the following method: The coupling agent and deionized water were mixed evenly in a mass ratio of 2:100, and allowed to stand at room temperature for 1 hour. Then, 5% of the mass of the coupling agent, hexamethylene diisocyanate, was added, and ultrasonic dispersion was performed for 15 minutes to obtain a coupling agent solution.

[0076] The coupling agent is isopropyl titanate triisostearate and γ-aminopropyl triethoxysilane in a mass ratio of 1:1.

[0077] Wherein, the modified graphene oxide is prepared by the following method: The mass ratio of graphene oxide to N,N-dimethylformamide solution was controlled to be 1:300, and graphene oxide was dispersed in 40% by mass N,N-dimethylformamide solution. The mixture was ultrasonically dispersed at 40 kHz for 25 min, and hydroxyethyl acrylate, hydroquinone and azobisisobutyronitrile were added. The mixture was heated to 100°C, reacted for 8 h, concentrated under reduced pressure, and dried at 60°C for 6 h to obtain modified graphene oxide, wherein the mass ratio of graphene oxide, hydroxyethyl acrylate, hydroquinone and azobisisobutyronitrile was 1:0.5:0.1:0.2.

[0078] Wherein, the diluent is butyl glycidyl ether.

[0079] The curing agent is 4,4'-diaminodiphenylmethane and triglycidyl isocyanurate in a mass ratio of 2:0.5.

[0080] Among them, the leveling agent is BYK-310.

[0081] Wherein, the curing accelerator is 2-methylimidazole.

[0082] A method for preparing a modified rare earth mineral negative ion indoor coating comprises the following steps: S1, weighing the raw materials in parts by mass; S2, adding a diluent to the epoxy resin and the polyurethane resin, stirring at 300 rpm for 8 min to obtain a mixed resin; S3, stirring the modified negative ion powder, modified graphene oxide and deionized water at 300 rpm for 25 min to obtain a mixed slurry; S4, stirring the mixed resin and mixed slurry at 60° C. and 200 rpm for 15 min to obtain a mixture, adding a curing agent, a leveling agent and a curing accelerator to the mixture, stirring at 50° C. and 300 rpm for 12 min to obtain a coating, and uniformly coating the coating on the surface of the substrate to obtain a modified rare earth mineral anion indoor coating.

[0083] Comparative Example 3 A modified rare earth mineral negative ion indoor coating, comprising the following raw materials in parts by weight: 50 parts of epoxy resin, 10 parts of polyurethane resin, 15 parts of modified negative ion powder, 8 parts of modified graphene oxide, 15 parts of curing agent, 1 part of curing accelerator, 10 parts of diluent, 0.5 parts of leveling agent, and 25 parts of deionized water.

[0084] Wherein, the modified anion powder is prepared by the following method: A1. Weigh 2.0 parts of cerium nitrate, 0.5 parts of cobalt nitrate, 1.5 parts of lanthanum nitrate and 40 parts of deionized water, and stir at 200 rpm for 8 min to obtain a mixed solution; A2. Mix the mixed solution, mixed powder and mixed acid in a mass ratio of 10:1:2, heat to 80°C, stir at 300 rpm for 2 hours, let stand for 3 hours, filter, and dry at 100°C for 4 hours to obtain the material, control the mass ratio of grinding medium, material and grinding solvent to 2.0:1:1.2, ball milling time 70 minutes, rotation speed 300 rpm, grinding medium is steel ball, steel ball diameter is 20 mm, grinding solvent is ethanol, then control the heating rate to 5°C / min, heat to 400°C, keep warm for 30 minutes, then heat to 1000°C at a rate of 10°C / min, calcine for 5 hours to obtain negative ion powder; A3. The negative ion powder is subjected to alkali treatment to obtain pretreated negative ion powder; the pretreated negative ion powder and the coupling agent solution are mixed in a mass ratio of 1:3, heated to 80°C, stirred at 300 rpm for 6 hours, then filtered, washed three times with deionized water, and dried at 60°C for 12 hours to obtain modified negative ion powder.

[0085] The mixed powder is attapulgite and tourmaline powder in a mass ratio of 0.8:2.0.

[0086] The mixed acid is acetic acid and oxalic acid in a mass ratio of 1:0.8.

[0087] Among them, the alkali treatment includes: preparing a sodium hydroxide solution with a mass fraction of 40%, mixing the sodium hydroxide solution and the negative ion powder in a mass ratio of 12:0.5, stirring at 45°C and a speed of 300rpm for 5 hours, then filtering, washing with ethanol 3 times, and drying at 80°C for 5 hours to obtain the pretreated negative ion powder.

[0088] Wherein, the coupling agent solution is prepared by the following method: The coupling agent and deionized water were mixed evenly in a mass ratio of 2:100, allowed to stand at room temperature for 1 hour, and ultrasonically dispersed for 15 minutes to obtain a coupling agent solution.

[0089] The coupling agent is isopropyl titanate triisostearate and γ-aminopropyl triethoxysilane in a mass ratio of 1:1.

[0090] Wherein, the modified graphene oxide is prepared by the following method: The mass ratio of graphene oxide to N,N-dimethylformamide solution was controlled to be 1:300, and graphene oxide was dispersed in 40% by mass N,N-dimethylformamide solution. The mixture was ultrasonically dispersed at 40 kHz for 25 min, and hydroxyethyl acrylate, hydroquinone and azobisisobutyronitrile were added. The mixture was heated to 100°C, reacted for 8 h, concentrated under reduced pressure, and dried at 60°C for 6 h to obtain modified graphene oxide, wherein the mass ratio of graphene oxide, hydroxyethyl acrylate, hydroquinone and azobisisobutyronitrile was 1:0.5:0.1:0.2.

[0091] Wherein, the diluent is butyl glycidyl ether.

[0092] The curing agent is 4,4'-diaminodiphenylmethane and triglycidyl isocyanurate in a mass ratio of 2:0.5.

[0093] Among them, the leveling agent is BYK-310.

[0094] Wherein, the curing accelerator is 2-methylimidazole.

[0095] A method for preparing a modified rare earth mineral negative ion indoor coating comprises the following steps: S1, weighing the raw materials in parts by mass; S2, adding a diluent to the epoxy resin and the polyurethane resin, stirring at 300 rpm for 8 min to obtain a mixed resin; S3, stirring the modified negative ion powder, modified graphene oxide and deionized water at 300 rpm for 25 min to obtain a mixed slurry; S4, stirring the mixed resin and mixed slurry at 60° C. and 200 rpm for 15 min to obtain a mixture, adding a curing agent, a leveling agent and a curing accelerator to the mixture, stirring at 50° C. and 300 rpm for 12 min to obtain a coating, and uniformly coating the coating on the surface of the substrate to obtain a modified rare earth mineral anion indoor coating.

[0096] Comparative Example 4 A modified rare earth mineral negative ion indoor coating, comprising the following raw materials in parts by weight: 50 parts of epoxy resin, 10 parts of polyurethane resin, 15 parts of modified negative ion powder, 8 parts of modified graphene oxide, 15 parts of curing agent, 1 part of curing accelerator, 10 parts of diluent, 0.5 parts of leveling agent, and 25 parts of deionized water.

[0097] Wherein, the modified anion powder is prepared by the following method: A1. Weigh 2.0 parts of cerium nitrate, 0.5 parts of cobalt nitrate, 1.5 parts of lanthanum nitrate and 40 parts of deionized water, and stir at 200 rpm for 8 min to obtain a mixed solution; A2. Mix the mixed solution, mixed powder and mixed acid in a mass ratio of 10:1:2, heat to 80°C, stir at 300 rpm for 2 hours, let stand for 3 hours, filter, and dry at 100°C for 4 hours to obtain the material, control the mass ratio of grinding medium, material and grinding solvent to 2.0:1:1.2, ball milling time 70 minutes, rotation speed 300 rpm, grinding medium is steel ball, steel ball diameter is 20 mm, grinding solvent is ethanol, then control the heating rate to 5°C / min, heat to 400°C, keep warm for 30 minutes, then heat to 1000°C at a rate of 10°C / min, calcine for 5 hours to obtain negative ion powder; A3. The negative ion powder is subjected to alkali treatment to obtain pretreated negative ion powder; the pretreated negative ion powder and the coupling agent solution are mixed in a mass ratio of 1:3, heated to 80°C, stirred at 300 rpm for 6 hours, then filtered, washed three times with deionized water, and dried at 60°C for 12 hours to obtain modified negative ion powder.

[0098] The mixed powder is attapulgite and tourmaline powder in a mass ratio of 0.8:2.0.

[0099] The mixed acid is acetic acid and oxalic acid in a mass ratio of 1:0.8.

[0100] Among them, the alkali treatment includes: preparing a sodium hydroxide solution with a mass fraction of 40%, mixing the sodium hydroxide solution and the negative ion powder in a mass ratio of 12:0.5, stirring at 45°C and a speed of 300rpm for 5 hours, then filtering, washing with ethanol 3 times, and drying at 80°C for 5 hours to obtain the pretreated negative ion powder.

[0101] Wherein, the coupling agent solution is prepared by the following method: The coupling agent and deionized water were mixed evenly in a mass ratio of 2:100, and allowed to stand at room temperature for 1 hour. Then, 5% of the mass of the coupling agent, hexamethylene diisocyanate, was added, and ultrasonic dispersion was performed for 15 minutes to obtain a coupling agent solution.

[0102] The coupling agent is isopropyl titanate triisostearate and γ-aminopropyl triethoxysilane in a mass ratio of 1:1.

[0103] Wherein, the modified graphene oxide is prepared by the following method: The mass ratio of graphene oxide to N,N-dimethylformamide solution was controlled to be 1:300, and graphene oxide was dispersed in 40% by mass N,N-dimethylformamide solution. Ultrasonic dispersion was carried out at 40 kHz for 25 min, and hydroxyethyl acrylate and hydroquinone were added. The mixture was heated to 100°C, reacted for 8 h, concentrated under reduced pressure, and dried at 60°C for 6 h to obtain modified graphene oxide, wherein the mass ratio of graphene oxide, hydroxyethyl acrylate and hydroquinone was 1:0.5:0.1.

[0104] Wherein, the diluent is butyl glycidyl ether.

[0105] The curing agent is 4,4'-diaminodiphenylmethane and triglycidyl isocyanurate in a mass ratio of 2:0.5.

[0106] Among them, the leveling agent is BYK-310.

[0107] Wherein, the curing accelerator is 2-methylimidazole.

[0108] A method for preparing a modified rare earth mineral negative ion indoor coating comprises the following steps: S1, weighing the raw materials in parts by mass; S2, adding a diluent to the epoxy resin and the polyurethane resin, stirring at 300 rpm for 8 min to obtain a mixed resin; S3, stirring the modified negative ion powder, modified graphene oxide and deionized water at 300 rpm for 25 min to obtain a mixed slurry; S4, stirring the mixed resin and mixed slurry at 60° C. and 200 rpm for 15 min to obtain a mixture, adding a curing agent, a leveling agent and a curing accelerator to the mixture, stirring at 50° C. and 300 rpm for 12 min to obtain a coating, and uniformly coating the coating on the surface of the substrate to obtain a modified rare earth mineral anion indoor coating.

[0109] Comparative Example 5 A modified rare earth mineral negative ion indoor coating, comprising the following raw materials in parts by weight: 50 parts of epoxy resin, 10 parts of polyurethane resin, 15 parts of modified negative ion powder, 8 parts of modified graphene oxide, 15 parts of curing agent, 1 part of curing accelerator, 10 parts of diluent, 0.5 parts of leveling agent, and 25 parts of deionized water.

[0110] Wherein, the modified anion powder is prepared by the following method: A1. Weigh 2.0 parts of cerium nitrate, 0.5 parts of cobalt nitrate, 1.5 parts of lanthanum nitrate and 40 parts of deionized water, and stir at 200 rpm for 8 min to obtain a mixed solution; A2. Mix the mixed solution, mixed powder and mixed acid in a mass ratio of 10:1:2, heat to 80°C, stir at 300 rpm for 2 hours, let stand for 3 hours, filter, and dry at 100°C for 4 hours to obtain the material, control the mass ratio of grinding medium, material and grinding solvent to 2.0:1:1.2, ball milling time 70 minutes, rotation speed 300 rpm, grinding medium is steel ball, steel ball diameter is 20 mm, grinding solvent is ethanol, then control the heating rate to 5°C / min, heat to 400°C, keep warm for 30 minutes, then heat to 1000°C at a rate of 10°C / min, calcine for 5 hours to obtain negative ion powder; A3. The negative ion powder is subjected to alkali treatment to obtain pretreated negative ion powder; the pretreated negative ion powder and the coupling agent solution are mixed in a mass ratio of 1:3, heated to 80°C, stirred at 300 rpm for 6 hours, then filtered, washed three times with deionized water, and dried at 60°C for 12 hours to obtain modified negative ion powder.

[0111] The mixed powder is attapulgite and tourmaline powder in a mass ratio of 0.8:2.0.

[0112] The mixed acid is acetic acid and oxalic acid in a mass ratio of 1:0.8.

[0113] Among them, the alkali treatment includes: preparing a sodium hydroxide solution with a mass fraction of 40%, mixing the sodium hydroxide solution and the negative ion powder in a mass ratio of 12:0.5, stirring at 45°C and a speed of 300rpm for 5 hours, then filtering, washing with ethanol 3 times, and drying at 80°C for 5 hours to obtain the pretreated negative ion powder.

[0114] Wherein, the coupling agent solution is prepared by the following method: The coupling agent and deionized water were mixed evenly in a mass ratio of 2:100, and allowed to stand at room temperature for 1 hour. Then, 5% of the mass of the coupling agent, hexamethylene diisocyanate, was added, and ultrasonic dispersion was performed for 15 minutes to obtain a coupling agent solution.

[0115] The coupling agent is isopropyl titanate triisostearate and γ-aminopropyl triethoxysilane in a mass ratio of 1:1.

[0116] Wherein, the modified graphene oxide is prepared by the following method: The mass ratio of graphene oxide to N,N-dimethylformamide solution was controlled to be 1:300, and graphene oxide was dispersed in 40% by mass N,N-dimethylformamide solution. Ultrasonic dispersion was carried out at 40 kHz for 25 min, and hydroxyethyl acrylate and azobisisobutyronitrile were added. The mixture was heated to 100°C, reacted for 8 h, concentrated under reduced pressure, and dried at 60°C for 6 h to obtain modified graphene oxide, wherein the mass ratio of graphene oxide, hydroxyethyl acrylate and azobisisobutyronitrile was 1:0.5:0.2.

[0117] Wherein, the diluent is butyl glycidyl ether.

[0118] The curing agent is 4,4'-diaminodiphenylmethane and triglycidyl isocyanurate in a mass ratio of 2:0.5.

[0119] Among them, the leveling agent is BYK-310.

[0120] Wherein, the curing accelerator is 2-methylimidazole.

[0121] A method for preparing a modified rare earth mineral negative ion indoor coating comprises the following steps: S1, weighing the raw materials in parts by mass; S2, adding a diluent to the epoxy resin and the polyurethane resin, stirring at 300 rpm for 8 min to obtain a mixed resin; S3, stirring the modified negative ion powder, modified graphene oxide and deionized water at 300 rpm for 25 min to obtain a mixed slurry; S4, stirring the mixed resin and mixed slurry at 60° C. and 200 rpm for 15 min to obtain a mixture, adding a curing agent, a leveling agent and a curing accelerator to the mixture, stirring at 50° C. and 300 rpm for 12 min to obtain a coating, and uniformly coating the coating on the surface of the substrate to obtain a modified rare earth mineral anion indoor coating.

[0122] Performance Testing The comprehensive properties of the modified rare earth mineral negative ion indoor wall material coatings prepared in Examples 1-3 of the present application and Comparative Examples 1-5 were tested respectively.

[0123] According to the standard JC / T 2040-2010, the amount of negative ions generated in the air should be no less than 500 · (s· cm 2 ) -1 .

[0124] The antibacterial property is tested according to GB / T 21866-2008.

[0125] The antimicrobial persistence is tested according to HG / T 3950-2007, and the antimicrobial persistence of Class I antimicrobial coatings should be ≥95%.

[0126] The corrosion resistance is tested according to GB / T 1766-2008.

[0127] The waterproofness is tested according to GB / T 16777-2008, applying a water pressure of 0.3MPa for 120min.

[0128] Adhesion was tested according to ASTM D3359-17.

[0129] Hardness is tested according to GB / T 6379-2006.

[0130] Table 1 Performance test results of Examples 1-3 and Comparative Examples 1-5

[0131] It can be seen from the test results in the above table that the modified rare earth mineral negative ion indoor wall material coatings prepared in Examples 1-3 of the present invention have better air purification effects and good waterproof performance. The antibacterial effect is good, the antibacterial durability is high, and the wall material coating has good adhesion to the wall material. It is not easy to bubble, peel, or crack during use, and the color and luster remain stable. Compared with Comparative Example 1, the addition of cobalt ions significantly improves the antibacterial effect and durability of the coating; by comparing Example 1 with Comparative Examples 4-5, it can be found that the functionalization treatment of graphene oxide plays a key role in improving the antibacterial performance and stability of the wall material coating. In general, the introduction of modified negative ion powder and modified graphene oxide optimizes the comprehensive performance of the coating, making it more widely used in practical applications.

[0132] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A modified rare earth mineral negative ion indoor coating, characterized in that: The invention comprises the following raw materials in parts by weight: 50-70 parts of epoxy resin, 10-15 parts of polyurethane resin, 15-25 parts of modified negative ion powder, 8-12 parts of modified graphene oxide, 15-20 parts of curing agent, 1-4 parts of curing accelerator, 10-15 parts of diluent, 0.5-2.0 parts of leveling agent and 25-40 parts of deionized water.

2. A modified rare earth mineral negative ion indoor coating according to claim 1, characterized in that: The modified anion powder is prepared by the following method: A1. Weigh 2.0-6.0 parts of cerium nitrate, 0.5-1.0 parts of cobalt nitrate, 1.5-3.5 parts of lanthanum nitrate and 40-60 parts of deionized water, and mix them evenly to obtain a mixed solution; A2. Evenly mix the mixed solution, mixed powder and mixed acid in a mass ratio of 10:1-4:2-6, heat to 80-100°C, stir for 1-2h, let stand for 2-3h, filter, dry the material, ball mill and calcine to obtain negative ion powder; A3. Treat the anion powder with alkali to obtain pretreated anion powder; mix the pretreated anion powder and the coupling agent solution in a mass ratio of 1:1-3, heat to 80-100°C, stir for 4-6h, filter, wash, and dry to obtain modified anion powder.

3. A modified rare earth mineral anion indoor coating according to claim 2, characterized in that: The mixed powder is attapulgite and tourmaline powder in a mass ratio of 0.8-1.5:2.0-4.

0.

4. A modified rare earth mineral negative ion indoor coating according to claim 2, characterized in that: The mixed acid is acetic acid and oxalic acid in a mass ratio of 1:0.8-1.

5.

5. The modified rare earth mineral negative ion indoor coating according to claim 2, characterized in that: The calcination in step A2 specifically includes: First, control the heating rate to 5-8°C / min, heat to 400-500°C, keep warm for 30min-45min, then heat to 1000-1100°C at a rate of 10-15°C / min, and calcine for 3-5h.

6. The modified rare earth mineral anion indoor coating according to claim 2, characterized in that: The alkali treatment is specifically as follows: preparing a sodium hydroxide solution with a mass fraction of 40-60%, mixing the sodium hydroxide solution and the negative ion powder in a mass ratio of 12:0.5-2.5, stirring at 45-60°C for 3-5h, then filtering, washing, and drying at 80-100°C to obtain the pretreated negative ion powder.

7. The modified rare earth mineral anion indoor coating according to claim 2, characterized in that: The coupling agent solution is prepared by the following method: The coupling agent and deionized water are mixed evenly at a mass ratio of 2-5:100, and allowed to stand at room temperature for 1-2 hours. Then, 2-5% of the mass of the coupling agent, hexamethylene diisocyanate, is added, and ultrasonic dispersion is performed for 10-15 minutes to obtain a coupling agent solution.

8. The modified rare earth mineral negative ion indoor coating according to claim 7, characterized in that: The coupling agent is isopropyl titanate triisostearate and γ-aminopropyl triethoxysilane in a mass ratio of 1-3:1-3.

9. The modified rare earth mineral anion indoor coating according to claim 1, characterized in that: The modified graphene oxide is prepared by the following method: The graphene oxide is dispersed in a 40-60% by mass N, N-dimethylformamide solution, ultrasonically dispersed for 15-25 minutes, hydroxyethyl acrylate, hydroquinone and azobisisobutyronitrile are added, heated to 100-120° C., reacted for 6-8 hours, concentrated under reduced pressure, and dried to obtain modified graphene oxide.

10. A method for preparing a modified rare earth mineral negative ion indoor coating according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1, weighing the raw materials in parts by mass; S2, adding diluent to epoxy resin and polyurethane resin, stirring for 5-8 minutes to obtain mixed resin; S3, stirring the modified negative ion powder, modified graphene oxide and deionized water for 15-25 minutes to obtain a mixed slurry; S4, stirring the mixed resin and mixed slurry at 60-80° C. for 10-15 min to obtain a mixture, adding a curing agent, a leveling agent and a curing accelerator to the mixture, heating and stirring to obtain a coating, and uniformly coating the coating on the surface of the substrate to obtain a modified rare earth mineral anion indoor coating.